Public Discourse on Environmental Pollution and Health in Korea: Tweets Following the Fukushima Nuclear Accident - Kim, Seung-Hoi; Ha, Yu-i; Cha, Meeyoung; Lee, Jiyon; Kim, Byoung-Jik; Lee, Dong-Myung (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Public discourse on environmental and health issues has risenon social media. Upon an environmental crisis, various chatterssuch as breaking news, misinformation, and rumor couldaggravate social confusion and proliferate negative publicsentiment. In an effort to study public sentiments on environmentalissues in South Korea, we analyzed 158,964 tweetsgenerated over a 4-year period following the Fukushima accidentin 2011, the largest release of radioactivity to environmentin recent history. This event led to a significant increasein public’s interest on environmental and nuclear issues inKorea. We employed Bayesian network and recursive partitioningto observe the classification regression tree structureof major topics. Topics on health and environment were interlinkedclosely and represented both apprehension and concernabout health threats and pollution. Our methodologyhelps analyze large online discourse efficiently and offers insightto crisis response organizations.